1986
DOI: 10.1093/jnci/77.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Among Women Given X-Ray Therapy for Acute Postpartum Mastitis2

Abstract: Acute postpartum mastitis (APM) is an inflammatory-infectious condition of the breast, occurring commonly at childbirth or during lactation. A series of 601 women who received x-ray therapy for APM during the 1940's or 1950's have been followed up by mail questionnaire, with medical verification of pertinent conditions, to ascertain their incidences of breast cancer. Control subjects consisted of a series with APM who did not receive irradiation, plus the female siblings of both the APM groups, for a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
2

Year Published

1995
1995
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(58 citation statements)
references
References 0 publications
2
53
0
2
Order By: Relevance
“…The working hypothesis of the mechanisms for carcinogenesis is that it is of single-cell origin (UNSCEAR, 1993). Also, the conclusion of a linear effect in the low-dose region accords with most other breast cancer studies in this field (Land et al, 1980;Shore et al, 1986;Miller et al, 1989;Boice et al, 1991;Tokunaga et al, 1994). At dose levels above 5 Gy a cell-killing effect became obvious (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The working hypothesis of the mechanisms for carcinogenesis is that it is of single-cell origin (UNSCEAR, 1993). Also, the conclusion of a linear effect in the low-dose region accords with most other breast cancer studies in this field (Land et al, 1980;Shore et al, 1986;Miller et al, 1989;Boice et al, 1991;Tokunaga et al, 1994). At dose levels above 5 Gy a cell-killing effect became obvious (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…This effect was best described by a loglinear dose term. Cell-killing effects have been documented in some other studies, as for example in the New York Mastitis Study (Shore et al, 1986), in which a significant downward curvature was observed at doses > 3 Gy. Other studies have not found this effect, but they have generally little information at high dose levels (Miller et al, 1989;Boice et al, 1991;Tokunaga et al, 1994).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Since then, an increased incidence of thyroid tumors has been observed in populations including atomic bomb survivors (Wood et al, 1969), inhabitants of regions a ected by a thermonuclear test (Conard et al, 1970), patients with a history of external radiation for benign or malignant conditions (Shore et al, 1985), and most recently, in children contaminated in Ukraine and Belarus as a consequence of the Chernobyl accident (Kazakov et al, 1992). In the latter case, most of the tumors appeared after a short latent period, and were papillary carcinomas which were assumed to be the consequence of the contamination of the exposed children by radioactive iodine isotopes.…”
Section: Introductionmentioning
confidence: 99%